2019
DOI: 10.1155/2019/5963607
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Overall Survival and Progression-Free Survival by the 18F-FDG PET/CT Radiomic Features in Patients with Primary Gastric Diffuse Large B-Cell Lymphoma

Abstract: Purpose. To determine whether the radiomic features of 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) contribute to prognosis prediction in primary gastric diffuse large B-cell lymphoma (PG-DLBCL) patients. Methods. This retrospective study included 35 PG-DLBCL patients who underwent PET/CT scans at West China Hospital before curative treatment. The volume of interest (VOI) was drawn around the tumor, and radiomic analysis of the PET and CT images, within the same VOI, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) can visibly and comprehensively assess the glucose metabolism of tissues and has been widely used in a variety of malignant tumors including gastric cancer and lymphoma. [ 14 16 ] Semi-quantitatively, the standard uptake value (SUV) and its derivatives, which correlate to the degree of FDG uptake in tissues, have been demonstrated to help differentiate gastric cancer from gastric lymphoma. [ 17 , 18 ] Nonetheless, FDG uptake has a wide range in both gastric cancer and gastric lymphoma, [ 15 , 17 , 19 ] which is partially due to the differences between pathological subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) can visibly and comprehensively assess the glucose metabolism of tissues and has been widely used in a variety of malignant tumors including gastric cancer and lymphoma. [ 14 16 ] Semi-quantitatively, the standard uptake value (SUV) and its derivatives, which correlate to the degree of FDG uptake in tissues, have been demonstrated to help differentiate gastric cancer from gastric lymphoma. [ 17 , 18 ] Nonetheless, FDG uptake has a wide range in both gastric cancer and gastric lymphoma, [ 15 , 17 , 19 ] which is partially due to the differences between pathological subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…The more often the pairs of pixels ( i , j ) with certain intensities and spatial relationships co-occur, the higher the energy is. A previous study including PET/CT images of 35 primary gastric DLBCL patients reported that energy GLCM failed to predict either the progression-free survival (PFS) or the overall survival (OS) [ 30 ]. However, this study focused on the prediction of the prognosis rather than the treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the limited evidence and the indeterminate choices of PET texture features, the value of PET TA in lymphoma remains unclear. Moreover, to the best of our knowledge, the application of PET TA in PGIL has been reported by only one study, which did not include intestinal PGIL-DLBCL [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…When S reg approaches zero the tumor will be highly irregular, resembling a fractal-like structure. This parameter receives different names in the literature and has been found to have prognostic value in lung cancer [ 39 , 40 ], head and neck cancer [ 41 , 42 ], esophageal cancer [ 43 ], breast cancer [ 44 ], lymphoma [ 45 ], and glioma [ 24 , 38 ].…”
Section: Methodsmentioning
confidence: 99%